The Effects of Garlic and Red Chilli Pepper Powder on Physicochemical, Microbiological, and Sensory Properties of Cincalok - Risa Nofiani; Novi Maulidi Syahmurdiandi; Puji Ardiningsih (International Journal of Food Science)
Cincalok, a traditional fermented shrimp, is prepared by mixing rebon shrimps (Acetes sp) with coarse salt and granulated sugar in a certain ratio. This research was aimed at studying the effect of adding garlic and red chilli pepper powder on the physicochemical, microbiological, and sensory properties of cincalok. Cincalok was made to be three recipes, namely, original cincalok, A, consists of 2 kg of rebon shrimp, 400 g of granulated sugar, and 100 g of coarse salt; B (A ingredients plus 20 g of red chilli pepper powder); and C (A ingredients plus 20 g of garlic powder). Sensory analysis was conducted on recipe A, and the colour was observed by the naked eye on days 0, 2, 4, 6, 8, 13, 18, 23, 28, 33, 43, 60, 90, 120, 150, and 180. According to the highest criterion score on sensory results, the panellists chose day 6 as the best fermentation for recipe A. The colour of recipe A started changing from pink to a light brown colour on the surface on day 28. Therefore, the physicochemical, microbiological, and sensory properties of each recipe were analyzed for 28 days. Overall, the water, ash, and fat content; titratable acid (TA); total volatile base nitrogen (TVBN); and amino acid nitrogen (AAN) showed insignificant differences (p>0.05) among the recipes during 28 days of the same observation. The crude protein, pH, and free fatty acid (FFA) of recipe C were significantly different (p<0.05) from recipes A and B. All recipes contained the total count of mesophilic anaerobic bacteria (TMABs) and the lactic acid bacteria (LABs) except Bacillus cereus, Clostridium perfringens, Staphylococcus aureus, and Enterobacteriaceae for all observation times. The highest criterion score for consumer acceptability was awarded for recipe C followed by recipes B and A. The addition of garlic and red chilli pepper powder affected the physicochemical, microbiological, and sensory properties of cincalok.